The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.12693/aphyspola.82.999
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Domains in NaNO2Crystals

Abstract: Growth and shrinkage of domains in sodium nitrite crystals are investigated in a wide range of electric fields using the liquid crystal method. The rhombic shape of domains in the growing process and the lenticular shape of domains in the shrinking process are observed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…On the other hand, analytical [9,10,11,12] and semi-analytical [13,14,15,16,17,18] approximations have been constructed and successfully applied in numerous physically interesting cases. Moreover, at the expense of increasing number of numerical data required to construct the stress-energy tensor, a few best-fit models has been proposed [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, analytical [9,10,11,12] and semi-analytical [13,14,15,16,17,18] approximations have been constructed and successfully applied in numerous physically interesting cases. Moreover, at the expense of increasing number of numerical data required to construct the stress-energy tensor, a few best-fit models has been proposed [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, all our current understanding of the stress-energy tensor of the quantized massless fields is limited to the static black holes described by the electric charge and the mass. Our results, however, may be of use in the linearized back reaction calculations [19,20]: the curved spacetime leads to the stress-energy tensor approximated by (9)(10)(11), which, in turn, modifies the background geometry.…”
mentioning
confidence: 87%
“…It has been shown that for both scalar and vector fields the approximation is reasonable. (Analytical approximation of tensor ∆ ν µ of the scalar field has been constructed in [9]). Unfortunately, as has been pointed out in Ref.…”
mentioning
confidence: 99%
“…[8,9] have been applied in the spactimes of the Reissner-Nordström [8] and dilaton black holes [16]. Various aspects of the backreaction problem have been studied in Refs.…”
Section: Introductionmentioning
confidence: 99%